Oxidative Phosphorylation-Mediated E-Selectin Upregulation Is Associated With Endothelia–Monocyte Adhesion in Human Coronary Artery Endothelial Cells Treated With Sera From Patients With Kawasaki Disease - Zhang, Danfeng; Liu, Lingjuan; Yuan, Yuxing; Lv, Tiewei; Huang, Xupei; Tian, Jie (Frontiers in Pediatrics, 2021)
Background and aims: E-selectin is a cell adhesion molecule of the vascular endothelium that mediates leukocyte rolling in the early inflammatory responses in many diseases including Kawasaki disease (KD). Previous studies have demonstrated that the expression levels of E-selectin was significantly increased in the sera of KD patients and in endothelial cells of KD patient's autopsy. In this study, we aimed to examine E-selectin levels in endothelial cells treated with sera from KD patients and explore the underlying mechanisms. Methods: Human coronary artery endothelial cells (HCAECs) were randomly incubated with sera from either healthy children [healthy control (HC group)] or pediatric KD patients [assigned as KD with coronary artery lesion (KD-CAL+ group) and KD without coronary artery lesion (KD-CAL– group)]. E-selectin levels were determined by RT-qPCR, Western blotting, and immunofluorescence. Cell adhesion assay was performed to quantify the role of E-selectin in intercellular adhesion. High-throughput cell RNA sequencing followed by functional validation was performed to explore the underlying mechanism. Results: E-selectin levels were significantly increased in KD-CAL+ group vs. HC group and KD-CAL– group. Compared with the KD-CAL– group, endothelia–monocyte adhesion was increased in the KD-CAL+ group, while E-selectin-specific siRNA could significantly rescue it. High-throughput cell RNA sequencing analysis also found a significant difference in oxidative phosphorylation (OXPHOS) levels between KD-CAL+ group and KD-CAL– group. Functional validation results further confirmed that the OXPHOS was upregulated in the KD-CAL+ group and KD-CAL– group compared to that in the HC group, while the KD-CAL+ group exhibited a higher OXPHOS than the KD-CAL– group. We also found that the E-selectin levels and endothelia–monocyte adhesion were significantly decreased by OXPHOS inhibitor oligomycin in the KD-CAL+ group and KD-CAL– group, respectively. Conclusion: Sera from KD patients stimulate OXPHOS levels and enhance E-selectin expression in HCAECs, which may contribute to the development of CAL in KD patients.